Absence of a neutralizing antibody response to humanized cobra venom factor in mice. (May 2018) - Ing, Mathieu; Hew, Brian E.; Fritzinger, David C.; Delignat, Sandrine; Lacroix-Desmazes, Sébastien; Vogel, Carl-Wilhelm; Rayes, Julie
Highlights: Humanized Cobra Venom Factor (hCVF) is a human C3 derivative with the CVF-like function of depleting complement. HCVF injected weekly for four weeks into mice induces the formation of IgG antibodies which cross-react with CVF and human C3. The antibody response to hCVF does not neutralize the activity of hCVF, allowing for repeated complement depletion. Abstract: Cobra venom factor (CVF) is the complement-activating protein in cobra venom. Humanized CVF (hCVF) is a human C3 derivative where the C-terminal 168 amino acid residues were replaced with the homologous sequence from CVF. hCVF has been shown in multiple models of disease with complement pathology to be a promising therapeutic agent, with no observed adverse effects. Here we describe the antibody response to hCVF in two different strains of mice. hCVF was able to repeatedly decomplement the mice after four injections in weekly intervals, demonstrating the absence of a neutralizing antibody response. In contrast, natural CVF caused decomplementation in all mice only after the first administration. After two additional administrations of natural CVF, decomplementation was inconsistent and varied tremendously from mouse to mouse. After the fourth administration, natural CVF was essentially unable to deplete complement, consistent with the known generation of a neutralizing antibody response. We also analyzed the IgG antibody response to hCVF. There was great variation, with approximately one quarter of the mice exhibiting non-detectable levels of anti-hCVF IgG, and another quarter very low levels. The levels of anti-hCVF IgG did not correlate with the levels of remaining C3. The anti-hCVF antibodies cross-reacted with natural CVF, recombinant CVF, and human C3. Whereas overall the level of anti-hCVF IgG cross-reacting with human C3 was lower compared to rCVF or nCVF, mice with higher levels of anti-hCVF IgG exhibited higher binding to CVF and human C3, excluding the possibility that higher antibody levels reflect preferential immunogenicity of CVF-specific or human C3-specific epitopes.